The condition of students' readiness of faculty of physical culture and human health to future professional activity - Temerivskaya T.G (Kharkov National Pedagogical University, 2010)
Condition of students' readiness to the innovations in professional activity of teacher of physical education is analysed. Possibility of further improvement is presented to professionally-pedagogical to activity of students. It is well-proven that for the increase of efficiency of forming of future teachers' of physical education readiness, more attention is important to spare the role of personality factor, motivational orientation, purposeful forming of necessities to professional activity.